Diagnostic yield of ultrasound-guided fine needle aspiration biopsy (US-guided FNAB) and post-surgical histopathological correlation of thyroid nodules in the Department of Radiology, Groote Schuur Hospital, Cape Town, South Africa over a two-year period - Matimati, Bornaventure (Division of Radiology, 2023)
Background: Nodular thyroid disease is common worldwide, and the incidence of thyroid nodules is increasing globally. Ultrasound (US)-guided thyroid nodule fine needle aspiration biopsy (FNAB) is a reliable and cost-effective method of distinguishing between benign and malignant nodules before major surgery is performed. Aims: The study aimed to establish the diagnostic yield of US-guided thyroid FNAB's done at Groote Schuur Hospital over two years and to correlate findings with histopathological results in those patients that underwent thyroidectomy. Objectives: The objectives were to establish the number of US-guided FNABs performed, the number of repeat FNABs and the number of patients who subsequently had thyroidectomy over two years. A further objective was to evaluate the diagnostic yield by comparing the cytology and histology results for patients that underwent thyroidectomy. Methods: This was a retrospective study of all patients referred for US-guided FNAB from 1 January 2018 to 31 December 2019. All patients with cytology results after FNAB and histology results after thyroidectomy, were included in the study. US-guided FNAB data was collected from the Picture Archiving and Communication System (PACS) and Radiology Information System (RIS), while cytology and histology data were obtained from the National Health Laboratory Services (NHLS). Results: A total of 236 patients were included in the study (220 females and 16 males), with ages ranging from 19 to 82 years. The diagnostic yield was 34-% on the first, 36-% on the second and 48-% on the third FNAB. Most of the US-guided FNABs were non-diagnostic (66- % on the first, 64-% on the second and 52-% on the third FNAB). A total of 107 patients (45 %) had a repeat FNAB, while 23 patients (9.7-%) had a second repeat FNAB. A total of 48 patients (20.3-%) underwent thyroidectomy. Cancer was detected in 29/236 (12.3-%), of which 17/29 (59-%) were papillary thyroid carcinomas. There was no significant correlation between FNAB results and post-surgical histopathological results in patients who underwent thyroidectomy, with a p value of .15. Conclusion: The overall cancer rate of 12.3-% was comparable with that of other institutions. 66-% of US-guided FNABs were non-diagnostic, while 34-% were diagnostic on the first FNAB with 45-% requiring a repeat second FNAB. The assistance of a cytopathologist during the biopsy has been known to result in fewer non-diagnostic results, avoiding repeat attempts. Further diagnostic and cost-effective analysis of cytopathology assistance in the US-guided FNAB for characterising thyroid nodules is advised.